Finite and non-finite verbs in political news: Israeli and Palestinians issues - Gani, Yoshua Hardjoni; Alam, Beny; Lutifyanti, Winda (LADU: Journal of Languages and Education, 2020)
Background: Â For centuries, newspapers have delivered news to the reading public informing important events of a day. Specifically, the political news nowadays is more relaxed and popular than other sections, not to mention that it is also presented in an interesting and serious manner.Purpose: This research aims to classify and determine the verbs whether they are finite or non-finite.Design and methods: The subjects of the research are political news of â€œThe Jakarta Postâ€ newspaper which have taken and collected from two articles published on Monday, January 27th, 2020 and Tuesday, January 28th, 2020, with the focus on news related to â€œDonald Trumpâ€™s issues between Israeli and Palestiniansâ€. The method used in the research is descriptive qualitative methodology. The main theory of this research are Greenbaum and Nelson (2009), Burton-Roberts (2011), and Lobeck and Denham (2014). The steps in analyzing the data include: (1) collecting the data, (2) categorizing the collected data into their own classifications, (3) analyzing the data, (4) determining the data whether they are finite or non-finite verbs, and finally (5) concluding the data.Results: The results of the research shows that from the total of two hundred and seventy-two findings, there are one hundred and twenty-eight data of finite verbs (47%) and one hundred and forty-four data of non-finite verbs which then are divided into thirty-one â€“to infinitives (12%), twenty-six bare infinitives (10%), twenty-three passive participles (8%), thirty â€“ing participles (11%), twelve passive participle forms of be (4%), nine progressive participle forms of be (3%), and thirteen perfect participle forms of have (5%).